Granulometric study of bean straw residue for beneficial effect in the process of obtaining bioethanol (Research, Society and Development, 2020)
Beans are a food present all over the world and, mainly, in the Northeast region for its diversified cuisine. As it is a raw material already cultivated in the Potiguar region and for a predominantly familiar agriculture, the residues formed by its straws, often have a correct or appropriate disposal. Thus, the present research analyzes the bean straw as a source for the generation of bioethanol, a cleaner, less toxic and renewable type of biofuel, compared to those derived from fossil fuels, in addition to proposing a use for this lignocellulosic biomass with less aggression to the environment. In this context, the work aims to employ the granulometric test in order to find a better contact surface between the particles of this biomass that provides an increase in the percentage of production in fermentable sugars, as well as to apply the acid hydrolysis technique as an essential tool for the production of bioethanol. The methodology followed was based on literature review and experimental tests. The use of the granulometric procedure and acid hydrolysis contributed to an increase in the sugar content in the bean straw sample, which was around 400% when compared to its initial sample (white sample), thus having great potential for alcohol production, becoming a promising source of energy.